An efficient strategy for modeling the human auditory system from Micro-Computed Tomography Imaging. - Caminos-Gámez, Luis Francisco; Chaves-Hernández, Gonzalo; Lima-Rodríguez, Antonia María; García-Manrique-Ocaña, José Manuel; González-Herrera, Antonio (My University, 2023)
Finite Element modeling is a widely used methodology to build numerical models and simulate the behavior of the human auditory system; this has allowed essential advances in understanding the biomechanics of that complex system. There are two key points in modeling: the construction of an adequate geometry that allows efficient meshing and the correct use of mechanical properties of the materials. This research aims to show a new strategy for automating the build Finite Element Model process of the human auditory system using the FEM from Micro-Computed Tomography (Micro-CT) Imaging. The idea behind this methodology is to build a Finite Element Model with a computational and temporal low cost. This work allowed us to design the first semi-automatic algorithm to build a finite element model of the human middle ear that will later be used to incorporate the other components of the auditory system for different types of studies.
Keywords: Oído - Imágenes por resonancia magnética; Tomografía; Human hearing; Middle ear; Finite element model